2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Florida Landlord-Tenant Law [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The Florida Landlord-Tenant Law defines terms for termination of tenancy by either party. This is EDIS document FE400, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.